Experimental search for the "impossible atoms" Pauli Exclusion Principle violation and spontaneous collapse of the wave function at test. (June 2015) - Curceanu, C; Bartalucci, S; Bassi, A; Bertolucci, S; Berucci, C; Bragadireanu, A M; Cargnelli, M; Clozza, A; De Paolis, L; Di Matteo, S; Donadi, S; d'Uffizi, A; et al.
Abstract: Many experiments investigated the possible violation of the Pauli Exclusion Principle (PEP) since its discovery in 1925. The VIP(Violation of the Pauli Principle) experiment tested the PEP by measuring the probability for an external electron to be captured and undergo a 2p to 1s transition during its cascading process, with the 1s state already occupied by two electrons. This transition is forbidden by the PEP. The VIP experiment resulted in an upper limit for the probability of PEP violation of 4.7 × 10 −29 . Currently a setup for the follow up experiment VIP2 is under preparation. The goal of this experiment is to improve the upper limit for the violation of the PEP by two orders of magnitude, by using new X-ray detectors and by implementing an active shielding. We then present the idea of using an analogous experimental technique to search for X rays as a signature of the spontaneous collapse of the wave function, predicted by the continuous spontaneous localization theories, and discuss some very encouraging preliminary results.